Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Beneficial use of contaminated sediments: a literature review of the state of practice in Europe and North America - John Toll; Eric Hedblom; Luca Sittoni; Arjan Widjeveldt; David Moore; Clifford Firstenberg; Steven Brown; Eric Dott (Journal of Soils and Sediments, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Volatilized Metabolites Produced by Soilborne Aspergillus flavus Regulate Fungal Conidiation, and Production of Secondary Metabolites - Lina Castano-Duque; Imtiaz Ahmad; Steven W. Lloyd; Matthew D. Lebar; Carol Carter-Wientjes; Nathaniel B. McCartney; Jared G. Ali; Geromy G. Moore (Journal of Chemical Ecology, 2026)
Corn plants are susceptible to infection by fungi such as Aspergillus flavus that have the potential to produce several types of mycotoxins, one of the most potent ones known to exist is aflatoxin. Since aflatoxin contaminated corn must be destroyed, causing annual monetary losses in billions of dollars, it would be helpful to detect the presence of aflatoxin producing fungi at pre-harvest and pre-planting stages. To this end, it may be possible to capture volatile organic compounds these fungi produce while overwintering in the soil or while infecting corn plants. In this study, we acquired A. flavus VOCs from conidia and sclerotia, while residing in the soil environment. We concluded that soilborne conidia and sclerotia have specific VOC signatures, and sclerotia tend to emit specific VOCs at greater abundance compared to soilborne conidia or fungus-free soil. These sclerotium-specific VOCs include geranyl acetone, caryophyllene compounds, and methanone. Bioassays using toxin producing and non-producing fungi showed that β-caryophyllene increased spore concentration, and both β-caryophyllene and caryophyllene oxide were able to modulate aerial hyphae, sclerotia production and decrease aflatoxin, cyclopiazonic acid and ditryptophenaline production in A. flavus strains. Our results show insights into the ecological roles that β-caryophyllene and caryophyllene oxide have over A. flavus’ development and metabolism, although their effect on multitrophic interactions among corn, fungi and other potential organisms are still not fully understood. These VOCs could serve as an agricultural surveillance management system that enables early mitigation of aflatoxin producing fungi outbreaks in the field.

Co-producing knowledge with Indigenous Peoples: challenges and solutions for academic institutions - Jaime Grimm; Madeline Jarvis-Cross; Megan Bailey; Natalie C. Ban; Mackenzie Bartlett; Rachael Cadman; Sara E. Cannon; Steven J. Cooke; Kristen Cyr; Veronique Dubos; Alexander Duncan; Joseph Gazing Wolf; et al. (Trends in Ecology & Evolution, 2026)

Seeing the forest for the trees: white spruce (Picea glauca) tree bark as a biogeochemical indicator of a lithium occurrence in southwestern New Brunswick, Canada - Alexandre Voinot; A.M. Mloszewska; Steven Rossiter; Lyndsay Moore; Sabrina Chan; Margaret Linttell; Steve Day (Science of The Total Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Intelligent weed management using aerial image processing and precision herbicide spraying: An overview - Armin Ehrampoosh; Pushpika Hettiarachchi; Anand Koirala; Jahan Hassan; Nahina Islam; Biplob Ray; Md Nurun Nabi; Mohamed Tolba; Abdul Md Mazid; Cheng-Yuan Xu; Nanjappa Ashwath; Pavel Dzitac; et al. (Crop Protection, 2025)

Gopher Tortoise (Gopherus polyphemus) burrow associate communities are depauperate in modified landscapes - George C. Brooks; Steven J. Goodman; William M. Moore; Houston C. Chandler; Nicholas M. Caruso; Jennifer A. Smith; Thomas A. Gorman; Carola A. Haas (Community Ecology, 2025)
The Gopher Tortoise ( Gopherus polyphemus ) is considered a keystone species because its burrows provide refuge for an entire suite of other species (hereafter burrow associates) that occupy the habitats in which it resides. The Gopher Tortoise has declined across its range in large part due to habitat loss and land use change resulting in burrow abandonment or reduced burrow density, and the concomitant negative effects on burrow associate diversity have been well documented. However, under scenarios where Gopher Tortoise populations persist in modified habitat, the effect on community associates has received considerably less attention. In such instances, vegetation changes drive the loss of associate species, not the lack of suitable burrows. Here, we evaluated associations between Gopher Tortoise burrows and vertebrate burrow associates within test ranges and forested sites on Eglin Air Force Base, Florida. Specifically, we (1) determined how vegetation composition varies between forested sandhills and military test ranges, and (2) compared species richness, diversity, and community composition of burrow associates between habitats. We found that vegetation composition surrounding Gopher Tortoise burrows is highly variable, but in general test ranges had a simpler habitat structure and less diverse native plant communities than forested sites. As a result, we show that although military test range sites contain Gopher Tortoise burrows at comparable or higher densities than sites in natural longleaf pine sandhills, the community of vertebrate burrow associates in test range sites appears to be depauperate. Our results highlight that concern over habitat modifications may be warranted even in instances where Gopher Tortoise populations appear to be persisting. In the context of management that seeks to be beneficial to a wide array of burrow associates, efforts aimed at bolstering Gopher Tortoise populations in forested sandhills would be most prudent.

Limited Regulation of Canopy Water Use Efficiency by Stomatal Behavior Under Drought Propagation - Feng Li; Qinchuan Xin; Chuixiang Yi; Steven A. Kannenberg; Julia K. Green; Mirco Migliavacca; David J. P. Moore; Armen R. Kemanian; Pierre Gentine; Paul C. Stoy; Fangyue Zhang; Yujiu Xiong; et al. (Global Change Biology, 2025)
Water use efficiency (WUE) is a critical ecosystem function and a key indicator of vegetation responses to drought, yet its temporal trajectories and underlying drivers during drought propagation remain insufficiently understood. Here, we examined the trajectories, interdependencies and drivers of multidimensional WUE metrics and their components (gross primary production (GPP), evapotranspiration, transpiration (T), and canopy conductance (Gc)) using a conceptual drought propagation framework. We found that even though the carbon assimilation efficiency per stomata increases during drought, the canopy‐level WUE (represented by transpiration WUE (TWUE)) declines, indicating that stomatal regulation operates primarily at the leaf level and cannot offset the drought‐induced reduction in WUE at the canopy scale. A stronger dependence on T and TWUE indicates that the water–carbon trade‐off relationship of vegetation more inclines toward water transport than carbon assimilation. Gc fails to prevent the sharp decline in GPP during drought and has limited capacity to suppress T, as reflected by the reduction magnitude and the threshold (the turning point at which a component shifts from a normal to drought‐responsive state). The primary drivers of the water–carbon relationship under drought propagation include vapor pressure deficit and hydraulic traits. Among plant functional types, grasslands show the strongest water–carbon fluxes in response to drought, whereas evergreen broadleaf forests exhibit the weakest response. These findings refine our comprehensive understanding of multidimensional ecosystem functional dynamics under drought propagation and enlighten how the physiological response of vegetation to drought affects the carbon and water cycles.

Is local air pollution concentration a moderator or mediator of the association between residential greenspace and pediatric asthma exacerbations? A longitudinal study of pediatric patients in Philadelphia, Pennsylvania - Yun-Ting Yen; Leah H. Schinasi; Brisa N. Sánchez; Steven Melly; Kari Moore; Christopher B. Forrest; Chén C. Kenyon; Michelle C. Kondo; Anneclaire J. De Roos (International Journal of Hygiene and Environmental Health, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Prediction of daily childhood asthma exacerbation from ambient meteorological, environmental risk factors and respiratory viruses, Philadelphia, PA, 2011 to 2016 - Wanyu Huang; Lucy F. Robinson; Amy H. Auchincloss; Leah H. Schinasi; Kari Moore; Steven Melly; Christopher B. Forrest; Chén C. Kenyon; Anneclaire J. De Roos (Environmental Science and Pollution Research, 2025)
Childhood asthma exacerbation has multiple risk factors that occur concurrently in the environment — including extreme meteorological conditions, air pollution, aeroallergens, and respiratory virus infections. Few studies have predicted asthma exacerbation based on multiple time-varying environmental risk factors, together. In this study, we constructed an autoregressive integrated moving average (ARIMA) model to predict “high-risk” days for childhood asthma exacerbation in Philadelphia, PA from 2011 to 2016, during the aeroallergen season of each year, using a total of 28,540 asthma exacerbation case events identified from electronic health record (EHR) data. We selected predictors from quantile weighted sum regression (gQWS), incorporating temporal lags and season-stratification (early- vs. late-season), which were entered subsequently into multivariable ARIMA models. We found that daily nitrogen dioxide (NO 2 ), as well as monthly rhinovirus and respiratory syncytial virus (RSV) infection levels, were higher on the predicted “high-risk” days, as compared to days with lower childhood asthma exacerbation risk. The model performed better for late-season asthma exacerbation (July to October) than for early season (March to June). Future work and continued research is needed to facilitate local health guidelines pertaining to childhood asthma exacerbation.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

The Genomic Signature and Transcriptional Response of Metal Tolerance in Brown Trout Inhabiting Metal‐Polluted Rivers - Josephine R. Paris; R. Andrew King; Joan Ferrer Obiol; Sophie Shaw; Anke Lange; Vincent Bourret; Patrick B. Hamilton; Darren Rowe; Lauren V. Laing; Audrey Farbos; Karen Moore; Mauricio A. Urbina; et al. (Molecular Ecology, 2025)
Industrial pollution is a major driver of ecosystem degradation, but it can also act as a driver of contemporary evolution. As a result of intense mining activity during the Industrial Revolution, several rivers across the southwest of England are polluted with high concentrations of metals. Despite the documented negative impacts of ongoing metal pollution, brown trout ( Salmo trutta L.) survive and thrive in many of these metal‐impacted rivers. We used population genomics, transcriptomics, and metal burdens to investigate the genomic and transcriptomic signatures of potential metal tolerance. RADseq analysis of six populations (originating from three metal‐impacted and three control rivers) revealed strong genetic substructuring between impacted and control populations. We identified selection signatures at 122 loci, including genes related to metal homeostasis and oxidative stress. Trout sampled from metal‐impacted rivers exhibited significantly higher tissue concentrations of cadmium, copper, nickel and zinc, which remained elevated after 11 days in metal‐free water. After depuration, we used RNAseq to quantify gene expression differences between metal‐impacted and control trout, identifying 2042 differentially expressed genes (DEGs) in the gill, and 311 DEGs in the liver. Transcriptomic signatures in the gill were enriched for genes involved in ion transport processes, metal homeostasis, oxidative stress, hypoxia, and response to xenobiotics. Our findings reveal shared genomic and transcriptomic pathways involved in detoxification, oxidative stress responses and ion regulation. Overall, our results demonstrate the diverse effects of metal pollution in shaping both neutral and adaptive genetic variation, whilst also highlighting the potential role of constitutive gene expression in promoting metal tolerance.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Expression and functional characterization of bovine receptor activator of NF-κB ligand (RANKL) - Ambre F. Chapuis; Omar A. Alfituri; Jayne C. Hope; Jo Stevens; Jo Moore; Kevin Mclean; Dorota Androscuk; Inga Dry (Veterinary Immunology and Immunopathology, 2024)

Electro-flocculation of aquaculture wastewater microalgal communities reduces nutrient loading - Angela Capper; Sanath Alahakoon; Christopher Aiken; Rafaela Nunes; Shaneel Chandra; Steven Moore (Bioresource Technology, 2024)

Evaluation of evidence for interaction between PM2.5 and aeroallergens on childhood asthma exacerbation in Philadelphia, PA, 2011 to 2016 - Wanyu Huang; Leah H. Schinasi; Chén C. Kenyon; Amy H. Auchincloss; Kari Moore; Steven Melly; Lucy F. Robinson; Christopher B. Forrest; Anneclaire J. De Roos (Environmental Research, 2023)

The mobility and fate of Cr during aging of ferrihydrite and ferrihydrite organominerals - Yao Zhao; Alba Otero-Fariña; Ke-Qing Xiao; Oliver W. Moore; Steven A. Banwart; Fu-Jun Ma; Qing-Bao Gu; Caroline L. Peacock (Geochimica et Cosmochimica Acta, 2023)

Development and Validation of a Western Blot Method to Quantify Mini-Dystrophin in Human Skeletal Muscle Biopsies - Catherine I. Soderstrom; Jennifer Larsen; Carolina Owen; David Gifondorwa; David Beidler; Florence H. Yong; Patricia Conrad; Hendrik Neubert; Steven A. Moore; Mohamed Hassanein (The AAPS Journal, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative muscular disease affecting roughly one in 5000 males at birth. The disease is often caused by inherited X-linked recessive pathogenic variants in the dystrophin gene, but may also arise from de novo mutations. Disease-causing variants include nonsense, out of frame deletions or duplications that result in loss of dystrophin protein expression. There is currently no cure for DMD and the few treatment options available aim at slowing muscle degradation. New advances in gene therapy and understanding of dystrophin (DYS) expression in other muscular dystrophies have opened new opportunities for treatment. Therefore, reliable methods are needed to monitor dystrophin expression and assess the efficacy of new therapies for muscular dystrophies such as DMD and Becker muscular dystrophy (BMD). Here, we describe the validation of a novel Western blot (WB) method for the quantitation of mini-dystrophin protein in human skeletal muscle tissues that is easy to adopt in most laboratory settings. This WB method was assessed through precision, accuracy, selectivity, dilution linearity, stability, and repeatability. Based on mini-DYS standard performance, the assay has a dynamic range of 0.5–15 ng protein (per 5 µg total protein per lane), precision of 3.3 to 25.5%, and accuracy of − 7.5 to 3.3%. Our stability assessment showed that the protein is stable after 4 F/T cycles, up to 2 h at RT and after 7 months at − 70°C. Furthermore, our WB method was compared to the results from our recently published LC–MS method. Graphical Abstract Workflow for our quantitative WB method to determine mini-dystrophin levels in muscle tissues (created in Biorender.com). Step 1 involves protein extraction from skeletal muscle tissue lysates from control, DMD, or BMD biospecimen. Step 2 measures total protein concentrations. Step 3 involves running gel electrophoresis with wild-type dystrophin (wt-DYS) from muscle tissue extracts alongside mini-dystrophin STD curve and mini-DYS and protein normalization with housekeeping GAPDH.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica - Bradley R. Moore; Steven J. Parker; Peter M. Marriott; Colin Sutton; Matthew H. Pinkerton (Frontiers in Marine Science, 2022)
The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of longline fisheries for Antarctic toothfish ( Dissostichus mawsoni ) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M . caml and M . whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collections. Macrourus caml was found to live longer, grow slower, and attain a larger maximum length than M . whitsoni , reaching at least 65 years of age and 97 cm total length (TL) vs. 43 years and 78 cm TL for M . whitsoni . In addition, M . caml attains a larger length for a given age and a greater weight for a given length. For each species, females of a given age were larger and reached a greater maximum age than males. Assuming that selectivity of the fishing gear is related to fish size, greater fishing pressure on females than males is likely, and was evidenced by female-biased sex ratios of both species. Estimates of natural and fishing mortality rates were low for both species. Despite having a shorter lifespan and attaining a smaller maximum length, M . whitsoni matured later in life and at larger lengths than M . caml . Although sampling opportunities are constrained seasonally due to sea ice cover, gonad staging and interannual patterns in gonadosomatic indices suggest prolonged spawning for both species, with available data indicating peak spawning during austral summer. The differences in life history observed between these two closely related and morphologically similar species illustrates the importance of understanding species-specific life histories to infer responses to exploitation, provide key biological inputs to inform parameters for future risk assessments and ecosystem models as well as baseline information for comparative work over both time and space, contribute to greater clarity in managing fisheries that interact with these two species, and further our understanding of grenadier life history.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Tissue Distribution of Mercury in the Bodies of Wild American Alligators (Alligator mississippiensis) from a Coastal Marsh in Louisiana (USA) - Liberty A. Moore; John W. Finger; David L. Haskins; Ruth M. Elsey; Steven B. Castleberry; Travis C. Glenn; Charles H. Jagoe; I. Lehr Brisbin (Archives of Environmental Contamination and Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Using lipid profiling to better characterize metabolic differences in apolipoprotein E (APOE) genotype among community-dwelling older Black men - Megan M. Marron; Steven C. Moore; Stacy G. Wendell; Robert M. Boudreau; Iva Miljkovic; Akira Sekikawa; Anne B. Newman (GeroScience, 2022)

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Decadal trends and ecological shifts in backwater lakes of a large floodplain river: Upper Mississippi River - Robert M. Burdis; Steven A. DeLain; Eric M. Lund; Megan J. C. Moore; Walter A. Popp (Aquatic Sciences, 2020)

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

RAD-Seq Analysis and in situ Monitoring of Nassau Grouper Reveal Fine-Scale Population Structure and Origins of Aggregating Fish - Krista D. Sherman; Josephine R. Paris; Robert Andrew King; Karen A. Moore; Craig P. Dahlgren; Lindy C. Knowles; Kristine Stump; Charles R. Tyler; Jamie R. Stevens (Frontiers in Marine Science, 2020)

Inflammation-related genes are associated with epigenetic aging in HIV - Erin E. Sundermann; Mariam A. Hussain; David J. Moore; Steven Horvath; David T. S. Lin; Michael S. Kobor; Andrew Levine (Journal of NeuroVirology, 2019)

Do corn-soybean rotations enhance decomposition of soil organic matter? - Steven J. Hall; Ann E. Russell; A’lece R. Moore (Plant and Soil, 2019)

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems - Steven A. Kannenberg; Kimberly A. Novick; M. Ross Alexander; Justin T. Maxwell; David J. P. Moore; Richard P. Phillips; William R. L. Anderegg (Global Change Biology, 2019)
Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (c) dendrochronological sampling biases. In order to link legacy effects from tree rings to whole forests, we leveraged a rich dataset from a Midwestern US forest that was severely impacted by a drought in 2012. At this site, we compiled tree‐ring records, leaf‐level gas exchange, eddy flux measurements, dendrometer band data, and satellite remote sensing estimates of greenness and leaf area before, during, and after the 2012 drought. After accounting for the relative abundance of tree species in the stand, we estimate that legacy effects led to ~10% reductions in tree‐ring width increments in the year following the severe drought. Despite this stand‐scale reduction in radial growth, we found that leaf‐level photosynthesis, gross primary productivity (GPP), and vegetation greenness were not suppressed in the year following the 2012 drought. Neither temporal asynchrony between radial growth and carbon uptake nor sampling biases could explain our observations of legacy effects in tree rings but not in GPP. Instead, elevated leaf‐level photosynthesis co‐occurred with reduced leaf area in early 2013, indicating that resources may have been allocated away from radial growth in conjunction with postdrought upregulation of photosynthesis and repair of canopy damage. Collectively, our results indicate that tree‐ring legacy effects were not observed in other canopy processes, and that postdrought canopy allocation could be an important mechanism that decouples tree‐ring signals from GPP.

More salt, please: global patterns, responses and impacts of foliar sodium in grasslands - E. T. Borer; E. M. Lind; J. Firn; E. W. Seabloom; T. M. Anderson; E. S. Bakker; L. Biederman; K. J. La Pierre; A. S. MacDougall; J. L. Moore; A. C. Risch; M. Schutz; et al. (Ecology Letters, 2019)
Sodium is unique among abundant elemental nutrients, because most plant species do not require it for growth or development, whereas animals physiologically require sodium. Foliar sodium influences consumption rates by animals and can structure herbivores across landscapes. We quantified foliar sodium in 201 locally abundant, herbaceous species representing 32 families and, at 26 sites on four continents, experimentally manipulated vertebrate herbivores and elemental nutrients to determine their effect on foliar sodium. Foliar sodium varied taxonomically and geographically, spanning five orders of magnitude. Site‐level foliar sodium increased most strongly with site aridity and soil sodium; nutrient addition weakened the relationship between aridity and mean foliar sodium. Within sites, high sodium plants declined in abundance with fertilisation, whereas low sodium plants increased. Herbivory provided an explanation: herbivores selectively reduced high nutrient, high sodium plants. Thus, interactions among climate, nutrients and the resulting nutritional value for herbivores determine foliar sodium biogeography in herbaceous‐dominated systems.

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Long‐term climate and competition explain forest mortality patterns under extreme drought - Derek J. N. Young; Jens T. Stevens; J. Mason Earles; Jeffrey Moore; Adam Ellis; Amy L. Jirka; Andrew M. Latimer (Ecology Letters, 2017)
Rising temperatures are amplifying drought‐induced stress and mortality in forests globally. It remains uncertain, however, whether tree mortality across drought‐stricken landscapes will be concentrated in particular climatic and competitive environments. We investigated the effects of long‐term average climate [i.e. 35‐year mean annual climatic water deficit (CWD)] and competition (i.e. tree basal area) on tree mortality patterns, using extensive aerial mortality surveys conducted throughout the forests of California during a 4‐year statewide extreme drought lasting from 2012 to 2015. During this period, tree mortality increased by an order of magnitude, typically from tens to hundreds of dead trees per km 2 , rising dramatically during the fourth year of drought. Mortality rates increased independently with average CWD and with basal area, and they increased disproportionately in areas that were both dry and dense. These results can assist forest managers and policy‐makers in identifying the most drought‐vulnerable forests across broad geographic areas.

Body mass index, physical activity, and television time in relation to mortality risk among endometrial cancer survivors in the NIH-AARP Diet and Health Study cohort - Hannah Arem; Ruth M. Pfeiffer; Steven C. Moore; Louise A. Brinton; Charles E. Matthews (Cancer Causes & Control, 2016)

The Effects of Biodiesel and Crude Oil on the Foraging Behavior of Rusty Crayfish, Orconectes rusticus - Ana M. Jurcak; Steven J. Gauthier; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2015)

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Social Cognition and Brain Morphology: Implications for Developmental Brain Dysfunction - David W. Evans; Steven M. Lazar; K. B. Boomer; Aaron D. Mitchel; Andrew M. Michael; Gregory J. Moore (Brain Imaging and Behavior, 2015)

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers - Li Shen; Paul M. Thompson; Steven G. Potkin; Lars Bertram; Lindsay A. Farrer; Tatiana M. Foroud; Robert C. Green; Xiaolan Hu; Matthew J. Huentelman; Sungeun Kim; John S. K. Kauwe; Qingqin Li; et al. (Brain Imaging and Behavior, 2014)

An active lifestyle is associated with better neurocognitive functioning in adults living with HIV infection - Pariya L. Fazeli; Steven Paul Woods; Robert K. Heaton; Anya Umlauf; Ben Gouaux; Debra Rosario; Raeanne C. Moore; Igor Grant; David J. Moore (Journal of NeuroVirology, 2014)

Water Table Regime Regulates Litter Decomposition in Restiad Peatlands, New Zealand - Beverley R. Clarkson; Tim R. Moore; Neil B. Fitzgerald; Danny Thornburrow; Corinne H. Watts; Steven Miller (Ecosystems, 2014)

Real-world impact of neurocognitive deficits in acute and early HIV infection - Katie L. Doyle; Erin E. Morgan; Sheldon Morris; Davey M. Smith; Susan Little; Jennifer E. Iudicello; Kaitlin Blackstone; David J. Moore; Igor Grant; Scott L. Letendre; Steven Paul Woods (Journal of NeuroVirology, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Vascular Endothelial Growth Factors A and C are Induced in the SVZ Following Neonatal Hypoxia–Ischemia and Exert Different Effects on Neonatal Glial Progenitors - Jennifer M. Bain; Lisamarie Moore; Zhihua Ren; Sophia Simonishvili; Steven W. Levison (Translational Stroke Research, 2013)

Substance use is a risk factor for neurocognitive deficits and neuropsychiatric distress in acute and early HIV infection - Erica Weber; Erin E. Morgan; Jennifer E. Iudicello; Kaitlin Blackstone; Igor Grant; Ronald J. Ellis; Scott L. Letendre; Susan Little; Sheldon Morris; Davey M. Smith; David J. Moore; Steven Paul Woods (Journal of NeuroVirology, 2013)

Identification of germline genomic copy number variation in familial pancreatic cancer - Wigdan Al-Sukhni; Sarah Joe; Anath C. Lionel; Nora Zwingerman; George Zogopoulos; Christian R. Marshall; Ayelet Borgida; Spring Holter; Aaron Gropper; Sara Moore; Melissa Bondy; Alison P. Klein; et al. (Human Genetics, 2012)

SLC39A2 and FSIP1 polymorphisms as potential modifiers of arsenic-related bladder cancer - Margaret R. Karagas; Angeline S. Andrew; Heather H. Nelson; Zhongze Li; Tracy Punshon; Alan Schned; Carmen J. Marsit; J. Steven Morris; Jason H. Moore; Anna L. Tyler; Diane Gilbert-Diamond; Mary-Lou Guerinot; et al. (Human Genetics, 2012)

Rapid Biomass Quality Determination of Corn Stover Using Near-Infrared Reflectance Spectroscopy - Patrick T. Murphy; Kenneth J. Moore; D. Raj Raman; Robert P. Anex; Steven L. Fales (BioEnergy Research, 2012)

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Effects of Galvanic vestibular stimulation on cognitive function - Valentina Dilda; Hamish G. MacDougall; Ian S. Curthoys; Steven T. Moore (Experimental Brain Research, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Letter to the Editor in Chief: Rebuttal to the Letter to the Editor in Chief by Jörg Rinklebe, Rainer Wennrich, Sibylle Mothes Concerning the Article “A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils” by Moore et al., DOI:10.1007/s11270-010-0691-7 - Christopher W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

Erratum to: A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils - Christopher W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils - Christopher. W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

Designing Interventions to Overcome Poor Numeracy and Improve Medication Adherence in Chronic Illness, Including HIV/Aids - John O. Moore; Edward W. Boyer; Steven Safren; Gregory K. Robbins; Edwin D. Boudreaux; Rochelle Rosen; Bruce Barton; Frank Moss (Journal of Medical Toxicology, 2011)

Stability and Broad-sense Heritability of Mineral Content in Potato: Zinc - Charles Raymond Brown; Kathleen G. Haynes; Martin Moore; Mark J. Pavek; Daniel C. Hane; Steven L. Love; Richard G. Novy; J. Creighton Miller (American Journal of Potato Research, 2011)

Postdiagnosis diet quality, the combination of diet quality and recreational physical activity, and prognosis after early-stage breast cancer - Stephanie M. George; Melinda L. Irwin; Ashley W. Smith; Marian L. Neuhouser; Jill Reedy; Anne McTiernan; Catherine M. Alfano; Leslie Bernstein; Cornelia M. Ulrich; Kathy B. Baumgartner; Steven C. Moore; Demetrius Albanes; et al. (Cancer Causes & Control, 2011)

Successful cognitive aging in persons living with HIV infection - Lauren Malaspina; Steven Paul Woods; David J. Moore; Colin Depp; Scott L. Letendre; Dilip Jeste; Igor Grant (Journal of NeuroVirology, 2011)

Age-related changes in the corpus callosum in early-onset bipolar disorder assessed using volumetric and cross-sectional measurements - Melissa Lopez-Larson; Janis L. Breeze; David N. Kennedy; Steven M. Hodge; Lena Tang; Constance Moore; Anthony J. Giuliano; Nikos Makris; Verne S. Caviness; Jean A. Frazier (Brain Imaging and Behavior, 2010)

Effects of head-down bed rest and artificial gravity on spatial orientation - Steven T. Moore; Hamish G. MacDougall; William H. Paloski (Experimental Brain Research, 2010)

Stability and Broad-Sense Heritability of Mineral Content in Potato: Iron - Charles Raymond Brown; Kathleen G. Haynes; Martin Moore; Mark J. Pavek; Dan C. Hane; Steven L. Love; Richard G. Novy; J. C. Miller (American Journal of Potato Research, 2010)

Designing science web sites - Kica Worrilow; Todd King; Raymond Walker; Mark E. Rose; William Moore; Steven Joy (Earth Science Informatics, 2010)

Quantifying structural physical habitat attributes using LIDAR and hyperspectral imagery - Robert K. Hall; Russell L. Watkins; Daniel T. Heggem; K. Bruce Jones; Philip R. Kaufmann; Steven B. Moore; Sandra J. Gregory (Environmental Monitoring and Assessment, 2009)

Hepatic P450 Enzyme Activity, Tissue Morphology and Histology of Mink (Mustela vison) Exposed to Polychlorinated Dibenzofurans - Jeremy N. Moore; John L. Newsted; Markus Hecker; Matthew J. Zwiernik; Scott D. Fitzgerald; Denise P. Kay; Xiaowei Zhang; Eric B. Higley; Lesa L. Aylward; Kerrie J. Beckett; Robert A. Budinsky; Steven J. Bursian; et al. (Archives of Environmental Contamination and Toxicology, 2009)

Prospective study of physical activity and the risk of ovarian cancer - Michael F. Leitzmann; Corinna Koebnick; Steven C. Moore; Kim N. Danforth; Louise A. Brinton; Albert R. Hollenbeck; Arthur Schatzkin; James V. Lacey (Cancer Causes & Control, 2009)

Cognitive Neuropsychology of HIV-Associated Neurocognitive Disorders - Steven Paul Woods; David J. Moore; Erica Weber; Igor Grant (Neuropsychology Review, 2009)

Characterization of Insertion Sites in Rainbow Papaya, the First Commercialized Transgenic Fruit Crop - Jon Y. Suzuki; Savarni Tripathi; Gustavo A. Fermín; Fuh-Jyh Jan; Shaobin Hou; Jimmy H. Saw; Christine M. Ackerman; Qingyi Yu; Michael C. Schatz; Karen Y. Pitz; Marcela Yépes; Maureen M. M. Fitch; et al. (Tropical Plant Biology, 2008)

Pitch and space maps of skilled cellists: accuracy, variability, and error correction - Jessie Chen; Marjorie H. Woollacott; Steven Pologe; George P. Moore (Experimental Brain Research, 2008)

Local Patterns of Nucleotide Polymorphism Are Highly Variable in the Selfing Species Arabidopsis thaliana - Richard C. Moore; M. Henry H. Stevens (Journal of Molecular Evolution, 2008)

Locomotor response to levodopa in fluctuating Parkinson’s disease - Steven T. Moore; Hamish G. MacDougall; Jean-Michel Gracies; William G. Ondo (Experimental Brain Research, 2008)

Germ-line DNA copy number variation frequencies in a large North American population - George Zogopoulos; Kevin C. H. Ha; Faisal Naqib; Sara Moore; Hyeja Kim; Alexandre Montpetit; Frederick Robidoux; Philippe Laflamme; Michelle Cotterchio; Celia Greenwood; Stephen W. Scherer; Brent Zanke; et al. (Human Genetics, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Modeling locomotor dysfunction following spaceflight with Galvanic vestibular stimulation - Steven T. Moore; Hamish G. MacDougall; Brian T. Peters; Jacob J. Bloomberg; Ian S. Curthoys; Helen S. Cohen (Experimental Brain Research, 2006)

Modeling postural instability with Galvanic vestibular stimulation - Hamish G. MacDougall; Steven T. Moore; Ian S. Curthoys; F. Owen Black (Experimental Brain Research, 2006)

Physiological state of phytoplankton communities in the Southwest Atlantic sector of the Southern Ocean, as measured by fast repetition rate fluorometry - Claire L. Holeton; Florence Nédélec; Richard Sanders; Louise Brown; C. Mark Moore; David P. Stevens; Karen J. Heywood; Peter J. Statham; Cathy H. Lucas (Polar Biology, 2005)

Spatial orientation of optokinetic nystagmus and ocular pursuit during orbital space flight - Steven T. Moore; Bernard Cohen; Theodore Raphan; Alain Berthoz; Gilles Clment (Experimental Brain Research, 2005)

Overexpression of GSK3βS9A Resulted in Tau Hyperphosphorylation and Morphology Reminiscent of Pretangle-Like Neurons in the Brain of PDGSK3β Transgenic Mice - Baolin Li; John Ryder; Yuan Su; Steven A Moore Jr; Feng Liu; Patricia Solenberg; Kellie Brune; Niles Fox; Binhui Ni; Rugao Liu; Yan Zhou (Transgenic Research, 2004)

Tissue localization of the copper chaperone ATOX1 and its potential role in disease - Steven D.P. Moore; Karmon E. Helmle; Lisa M. Prat; Diane W. Cox (Mammalian Genome, 2002)

Epiphyte host preferences and host traits: mechanisms for species-specific interactions - Ragan M. Callaway; Kurt O. Reinhart; Georgianne W. Moore; Darrin J. Moore; Steven C. Pennings (Oecologia, 2002)

Assessing salt marsh health: A test of the utility of five potential indicators - Steven C. Pennings; V. Dan Wall; Darrin J. Moore; Mala Pattanayek; Tracy L. Buck; James J. Alberts (Wetlands, 2002)

Ocular counterrolling induced by centrifugation during orbital space flight - Gilles Clment; Steven T. Moore; Theodore Raphan; Bernard Cohen (Experimental Brain Research, 2001)

Zonation of shrubs in western Atlantic salt marshes - Steven C. Pennings; Darrin J. Moore (Oecologia, 2001)

Interaction of the body, head, and eyes during walking and turning - Takao Imai; Steven T. Moore; Theodore Raphan; Bernard Cohen (Experimental Brain Research, 2001)

Inter-chromophore interactions in pigment-modified and dimer-less bacterial photosynthetic reaction centers - Laura J. Moore; Steven G. Boxer (Photosynthesis Research, 1998)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)